Prognosis of Patients With Ischemic Stroke With Prior Anticoagulant Therapy: Direct Oral Anticoagulants Versus Warfarin - Kyeong‐Hyeon Chun; Hancheol Lee; Jung Hwa Hong; Kwon‐Duk Seo (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Direct oral anticoagulants (DOACs) have been the drug of choice for preventing ischemic stroke in patients with atrial fibrillation since 2014. In previous studies, the stroke risk while taking warfarin was 2 per 100 patient‐years and 1.5% per year while taking DOACs. We hypothesized that even if ischemic stroke occurred during anticoagulation therapy with DOACs, the prognosis was likely to be better than that with warfarin. Methods and Results Data from 2002 to 2019, sourced from a nationwide claims database, were used to identify atrial fibrillation patients using International Classification of Diseases codes. Patients who experienced an ischemic stroke during anticoagulation were categorized by the drugs used (warfarin, dabigatran, apixaban, rivaroxaban, and edoxaban). The primary outcome was mortality within 3 months and 1 year after the ischemic stroke. Among the 9578 patients with ischemic stroke during anticoagulation, 3343 received warfarin, and 6235 received DOACs (965 dabigatran, 2320 apixaban, 1702 rivaroxaban, 1248 edoxaban). The DOACs group demonstrated lower risks of 3‐month (adjusted hazard ratio [HR], 0.550, [95% CI, 0.473–0.639]; P<0.0001) and 1‐year mortality (adjusted HR, 0.596 [95% CI, 0.536–0.663]; P<0.0001) than the warfarin group. Apixaban and edoxaban within the DOAC group exhibited particularly reduced 1‐year mortality risk compared with other DOACs (P<0.0001). Conclusions Our study confirmed that DOACs have a better prognosis than warfarin after ischemic stroke. The apixaban and edoxaban groups had a lower risk of death after ischemic stroke than the other DOAC groups.